Splanchnic and systemic circulation cross talks: Implications for hemodynamic management of liver transplant recipients. Issue 1 (March 2020) - Mukhtar, Ahmed; Lotfy, Ahmed; Hussein, Amr; Fouad, Eman
Abstract : The interaction between splanchnic and systemic circulation has many hemodynamic and renal consequences during liver transplant. In a patient with liver cirrhosis, splanchnic vasodilatation causes arterial steal from the systemic circulation into the splanchnic bed, which decreases the effective blood volume. Moreover, rapid volume loading in these patients has less impact on the cardiac output because a higher proportion of infused fluid is shifted to the splanchnic area. Thus, in dissection phase, the traditional approach of volume loading to maintain intraoperative hemodynamic stability not only seems ineffective, but it may also aggravate surgical bleeding. Two approaches of volume therapy have been mentioned to maintain hemodynamic stability during liver transplantation: splanchnic volume reduction by volume restriction with or without phlebotomy to maintain low central venous pressure (CVP), and splanchnic decongestion using splanchnic vasoconstrictors. After reperfusion, an increase in the central blood volume was thought to have a deleterious effect on the new graft function; however, the precise central venous pressure value that causes hepatic congestion after reperfusion is unknown.